PENGARUH PENAMBAHAN BERBAGAI JENIS SUSU TERHADAP KARAKTERISTIK SOYGHURT - Mustika Nuramalia Handayani; Putri Wulandari (Agroindustrial Technology, University of Trunojoyo Madura, 2016)
Soyghurt is a kind of yogurt as functional food product obtained from the fermentation of lactic acid bacteria in soy milk. The fermentation process of soy milk is different from cow's milk fermentation, because of different carbohydrate content. Carbohydrates in soy milk is composed of oligosaccharide species that can not function optimally as a substrate of lactic acid bacteria. Therefore, fermented soy milk requires other carbohydrates, including sucrose and lactose of different types of milk. The aim of this study was to determine the effect of various types of milk in the manufacture soyghurt and determine the sensory and physicochemical characteristics of soyghurt. The method used in this study was a completely randomized design of experimental design which is the treatment factor is various types of milk used in the manufacture of soyghurt with three types of milk are skim milk, full cream milk, sweetened condensed milk. Soyghurt incubation in the fermentation process carried out at a temperature of 370C for 12 hours. The results showed that there were not significant differences in sensory characteristics of soyghurt with the addition of various types of milk. Soyghurt with the addition of sweetened condensed milk, is the most preferred panelists. It has viscosity 0.30 dPass, pH 3.97, protein content 7.44%, and fat content 7.07%.